Obstacles to sustainable development in the Islamic world - Ahmed Bsoul , Labeeb (Institut Agama Islam Negeri Ponorogo, 2024)
This study examines obstacles to sustainable development in the Islamic world through the lens of Islamic teachings and principles. Utilizing a qualitative research approach, this study selected relevant Islamic teachings on sustainability, cases of sustainable development in Islamic countries, and places facing specific challenges. Primary data were gathered from religious texts, whereas secondary data were collected from a comprehensive literature review, including the Quran, Hadith, and scholarly articles. The research process involved an extensive literature review and data analysis through data reduction to identify key themes, with a comparative analysis highlighting the differences and similarities between Islamic and non-Islamic countries' approaches. The key obstacles identified included corruption, social injustice, and wealth inequality. This study advocates for a comprehensive approach guided by scholars, policymakers, and local communities, involving the reinterpretation and implementation of Islamic values in development strategies. Education and awareness campaigns are proposed to empower individuals with the knowledge required to make ethical choices. By integrating scientific advancements with traditional wisdom, this study underscores the need to ensure that progress aligns with Islamic teachings of compassion, justice, and responsible stewardship.